The Effect of Outpatient Health Services on Patient Satisfaction at Puskesmas Indra Jaya, Indra Jaya District, Aceh Jaya Regency - Afriani, Rina; Asriwati, Asriwati; Nasution, Ramadhani Syafitri (Universitas Ibn Khaldun Bogor, 2024)
The quality of health services is defined as a condition that describes the level of perfection of the appearance of a health service product provided comprehensively. The dissatisfaction felt by patients when receiving services causes the quality of the health center to be poor. This research aims to analyze the influence of outpatient health services on patient satisfaction at the Indra Jaya Health Center, Aceh Jaya Regency. This type of research is an analytical survey with a cross-sectional approach using primary data with questionnaires and secondary data from Community Health Center reports. The population in this study were all outpatients who visited the Indra Jaya Health Center with a sample size of 95 people determined using the accidental sampling method. Analysis was carried out using univariate, bivariate, and multivariate analysis. The results of the logistic regression test show that the variables responsiveness (p=0.025), reliability (p=0.050), guarantee (p=0.150), concern (p=0.042), and physical evidence (p=0.073) influence patient satisfaction. The most influential variable is a concern with an Exp (B) value of 4.781. This research concludes that there is a positive influence between responsiveness and caring on patient satisfaction, while reliability, guarantee, and physical evidence do not have a significant influence. Therefore, efforts are needed to improve the quality of outpatient services by increasing attention to patients and providing good responses in responding to patient complaints.